Sicilia, un’isola dentro un continente umano - Puto, Małgorzata (Romanica Silesiana)
The analyzed text puts a great emphasis on the concept of an island perceived not only as a geographical autonomic zone, but also as a cultural and personal continuum. Culicchia’s novel focuses on the emotional and generational voyage preceded by the images that are alive in the mind of a child who now becomes an adult. Sicily is an example of the concept of mente locale which defines the relationship between space and human being for whom it is essential and primordial. Key words: Giuseppe Culicchia, island, voyage, identity, mente locale